2013
DOI: 10.1519/jsc.0b013e31827e8e78
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Recovery Status Scale Following High-Volume Muscle Damaging Resistance Exercise

Abstract: Currently no research has investigated the relationship between muscle damage, hormonal status, and perceived recovery scale (PRS). Therefore, the purpose of this study was to determine the effects of a high-volume training session on PRS and to determine the relationship between levels of testosterone, cortisol, and creatine kinase (CK) and PRS. Thirty-five trained subjects (21.3 ± 1.9 years) were recruited. All subjects participated in a high-volume resistance training session consisting of 3 sets of full sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
3
44
0
4
Order By: Relevance
“…Before each trial (day) subjects indicated a score on the PRS scale [24,35] (ranging from 0 to 10) indicating their subjective status of physical recovery. The PRS scale is a 0-10 scalar representation of varying levels of an individual's level of PRS, similar to an RPE scale.…”
Section: Rate Of Perceived Exertion (Rpe) and Perceived Recovery Statmentioning
confidence: 99%
“…Before each trial (day) subjects indicated a score on the PRS scale [24,35] (ranging from 0 to 10) indicating their subjective status of physical recovery. The PRS scale is a 0-10 scalar representation of varying levels of an individual's level of PRS, similar to an RPE scale.…”
Section: Rate Of Perceived Exertion (Rpe) and Perceived Recovery Statmentioning
confidence: 99%
“…It is worth noting however, that a myriad of factors tend to mediate perceptual measures with mediating factors themselves often not being mutually exclusive. Previous research suggests the PRS scale is a valid means of assessing perceptual feelings of recovery following repeated sprint bouts (25) and resistance exercise (33). However, to the author's knowledge, the current study is the first to investigate the effectiveness of the PRS scale in predicting performance following hypohydration, and while not definitive, current results offer introductory support to the idea that the PRS scale is sensitive to hypohydration.…”
Section: Discussionmentioning
confidence: 54%
“…Laurent et al (32) also indicated that if athletes provide scores from 0 to 2, 4 to 6, or 8 to 10, sport scientists should expect a declined performance, similar performance, or improved performance, respectively. Although not as widely accepted as session RPE, a recent study by Sikorski et al (46) indicated that the Perceived Recovery Status Scale is an effective tool to monitor recovery after heavy resistance training. By collecting information about the perceived recovery status of the athlete, sport scientists will be able to determine the level of fatigue that the previous games, practices, or workouts have caused the players.…”
Section: Perceived Recovery Statusmentioning
confidence: 99%
“…By collecting information about the perceived recovery status of the athlete, sport scientists will be able to determine the level of fatigue that the previous games, practices, or workouts have caused the players. Furthermore, this information may not only allow sport scientists to determine the readiness of players for particular workouts (32) but also allow for adjustments to be made based on the perceived recovery level of each player (46), potentially preventing an accumulation of fatigue that may lead to poor performance.…”
Section: Perceived Recovery Statusmentioning
confidence: 99%